Financial Literacy Education and Bookkeeping Practices for MSMEs through Literacy Community Collaboration: Edukasi Literasi Keuangan dan Praktik Pembukuan UMKM melalui Kolaborasi Komunitas Literasi - Triregina, Igara; Utari, Diah Siti; Susanti, Nova Yuni (Yayasan Ahmar Cendekia Indonesia, 2025)
To enhance the empowerment of MSMEs, particularly microenterprises, it is essential to strengthen financial literacy through bookkeeping training. This community service activity was initiated by a literacy-focused community in collaboration with volunteer speakers and conducted online via Zoom Meeting. The training covered basic financial literacy and practical bookkeeping, tailored to the needs of micro-businesses. Participants came from various regions, with the majority lacking a bookkeeping system. The session was designed to provide knowledge and simple financial management skills for business sustainability. The results showed that participants gained a better understanding of the importance of financial records and acquired initial competence in managing their business finances. Overall, the participants expressed satisfaction and enthusiasm, indicating that the training was relevant to the real conditions faced by MSMEs. This activity is expected to serve as an entry point for developing structured financial habits and encouraging long-term financial awareness among micro-entrepreneurs. Abstrak Dalam rangka meningkatkan keberdayaan UMKM, khususnya Usaha Mikro, diperlukan penguatan literasi keuangan melalui pelatihan sistem pembukuan sederhana. Kegiatan pengabdian kepada masyarakat ini diinisiasi oleh komunitas literasi yang berkolaborasi dengan narasumber volunteer dan dilaksanakan secara daring melalui platform Zoom Meeting. Materi pelatihan mencakup konsep dasar literasi keuangan dan praktik pencatatan keuangan yang disesuaikan dengan kebutuhan usaha mikro. Peserta berasal dari berbagai wilayah, dengan mayoritas belum memiliki sistem pembukuan usaha. Pelatihan ini dirancang untuk memberikan pengetahuan dan keterampilan awal dalam mengelola keuangan secara sederhana guna mendukung keberlanjutan usaha. Hasil kegiatan menunjukkan peningkatan pemahaman peserta terhadap pentingnya pencatatan keuangan serta kemampuan awal dalam menerapkannya. Secara umum, peserta memberikan tanggapan positif dan menyatakan bahwa pelatihan ini relevan dengan kondisi riil yang mereka hadapi. Kegiatan ini diharapkan menjadi langkah awal dalam membangun kebiasaan finansial yang tertib dan berkelanjutan bagi pelaku usaha mikro.